(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Organizations are facing various challenges, including the impact of their activities on the surrounding environment. Green accounting is a field of accounting that records, measures, and reports the environmental impact of a company’s operational activities, including costs and benefits. The implementation of green accounting has also begun at one of the BUMDes in Central Java, namely BUMDes Janti Jaya. Stakeholders are also suspected of having a strong influence in ensuring that the organization plays a good role in environmental management. This study aims to determine the role of stakeholders in the implementation of environmental accountability at BUMDes Janti Jaya. This study uses a qualitative descriptive approach with a case study method. Data collection was carried out through interviews in focus group discussion sessions. The data analysis method was carried out by developing a pentahelix model. Based on the research results, it can be seen that the implementation of environmental accounting has begun at BUMDes Janti Jaya, although there is not yet a major item in the financial report, but in the future it will be implemented. The involvement of internal and external stakeholders has actually occurred in overseeing the implementation of environmental accounting carried out by BUMDes. The involvement of internal stakeholders such as BUMDes administrators and external involvement in the pentahelix model occurs starting from five actors: academics, the private sector or business actors, the community, the government, and the media.